Cassell's German and English dictionary - Breul, Karl.; Betteridge, Harold T.; Cordes, Gerhard (London : Cassell, 1961)
This work has virtually been rewritten. Each entry has scrutinized for its relevance to learners and users of German in the post-war world.
Spine title: Cassell's German & English dictionary.
Includes index.
Includes bibliographical references: p. x-xi.
ne 31/08/2021
Ref.
Keywords: German language; English language